Reproductive Justice and Indigenous Women: Tethering Physicians to the Charter - Lombard, Alisa (Université d'Ottawa / University of Ottawa, 2023)
At the author’s request, the abstract has been removed due to the confidential nature of the thesis. It will be added once the embargo period has passed.